Inovasi Pelayanan Publik pada Program Website Sobat Dukcapil di Dinas Kependudukan dan Pencatatan Sipil Kota Tangerang (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to analyze public service innovation through the Sobat Dukcapil Website Program at the Tangerang City Population and Civil Registration Office in improving the quality of population administration services. The study uses a qualitative approach with data collection techniques in the form of interviews, observations, and documentation studies. The analysis was conducted using Everett M. Rogers' Diffusion of Innovations theory, which includes five characteristics of innovation, namely relative advantage, compatibility, complexity, trialability, and observability. The results show that the Sobat Dukcapil Website has relative advantages in terms of time efficiency, reduced queues, and easy access to online services. This innovation is also considered appropriate for the needs of urban communities and the Electronic-Based Government System (SPBE) policy. However, there are still obstacles in terms of complexity, particularly related to the digital literacy of the community and technical system disruptions.